Implementasi Literasi Membaca dalam Pembelajaran di Kelas 5B Pasca Covid-19 di SD Negeri 141 Pekanbaru - Febi Resvi Carmila; Zaka Hadikusuma Ramadan (Departement of Mathematics Education, 2023)
Reading literacy is an ability in which a person can understand, use, and reflect on texts through direct involvement to gain experience in order to achieve certain goals. The purpose of this study was to determine the implementation of reading literacy in learning in class 5B post-covid-19 at SDN 141 Pekanbaru, the supporting factors for reading literacy in learning in class 5B post-covid-19 at SDN 141 Pekanbaru, and the inhibiting factors for reading literacy in learning at class 5B post-covid-19 at SDN 141 Pekanbaru. The method used in this research is a qualitative method with a descriptive approach. Collecting data using observation techniques, interviews, and observations. Based on the results of the research, the implementation of reading literacy in learning in class 5B post-covid-19 at SDN 141 Pekanbaru has been well implemented. Starting from pre-reading activities, reading activities, and post-reading. The three activities are carried out by the teacher in stages according to the procedure. Teachers also include three stages of reading literacy in preparing lesson plans. In addition, schools also play a role in fostering students' reading literacy through platforms such as libraries and reading corners. This shows that students' reading literacy is facilitated in schools because teachers try to revive reading literacy and schools provide support to provide a platform so that students' reading literacy can increase.